High Precision Reference Position Generator for Motor Control in FPGA - Dvořák, Vojtěch (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
The paper deals with an architecture of a high precision reference position generator for a motor controller implemented in FPGA. The architecture was developed to achieve high accuracy and tunability with concern to resource efficient implementation in FPGA. Simulations of the proposed generator as well as synthesis results are presented in the paper.
Keywords: FPGA; Motor Controller; Synchronization